Eksistensi Kitab Musnad Rabi’ Bin Habib Sebagai Kitab Hadis Sahih Khawarij Al-Ibadiyah - Afro’ Anzali Nurizzati Arifah; Muhid; Isnaini Lu’lu’ Atim Muthoharoh; Zsazsa Tuhfa Khaira (USIM Press, 2025)
Journal Of Hadith Studies, Volume 10 Issue 1 Page (79–92)